2002
DOI: 10.1056/nejmoa013183
|View full text |Cite
|
Sign up to set email alerts
|

Salmeterol for the Prevention of High-Altitude Pulmonary Edema

Abstract: Prophylactic inhalation of a beta-adrenergic agonist reduces the risk of high-altitude pulmonary edema. Sodium-dependent absorption of liquid from the airways may be defective in patients who are susceptible to high-altitude pulmonary edema. These findings support the concept that sodium-driven clearance of alveolar fluid may have a pathogenic role in pulmonary edema in humans and therefore represent an appropriate target for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
252
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 360 publications
(268 citation statements)
references
References 26 publications
14
252
0
1
Order By: Relevance
“…Nevertheless, the failure of the Poon analysis to demonstrate any relationship between either mean or systolic Ppa and either the changes in EIT or FVC, while demonstrating a strong relationship between the changes in EIT or FVC and NPD, argues against the subclinical pulmonary edema seen in this study being of predominantly hydrostatic origin. This is also consistent with the work of Sartori et al (44), in which inhaled ␤ 2 -agonists, known to increase transepithelial sodium transport, decreased pulmonary edema in HAPE-susceptible individuals without any effect on pulmonary hemodynamics.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, the failure of the Poon analysis to demonstrate any relationship between either mean or systolic Ppa and either the changes in EIT or FVC, while demonstrating a strong relationship between the changes in EIT or FVC and NPD, argues against the subclinical pulmonary edema seen in this study being of predominantly hydrostatic origin. This is also consistent with the work of Sartori et al (44), in which inhaled ␤ 2 -agonists, known to increase transepithelial sodium transport, decreased pulmonary edema in HAPE-susceptible individuals without any effect on pulmonary hemodynamics.…”
Section: Discussionsupporting
confidence: 92%
“…Measurement of this NPD correlates well with the pathological changes seen in the airways of patients with cystic fibrosis (24). In a study of HAPEsusceptible individuals, Sartori et al (44) found that their NPD at sea level was 32% less negative than in non-HAPE-susceptible subjects and that, in addition, superperfusion with amiloride produced a significantly smaller depolarization in NPD in the HAPE-susceptible compared with the HAPE-resistant subjects. This work was extended by Mairbä url et al (30), who confirmed a less negative NPD in HAPE-susceptible individuals, compared with nonsusceptible controls at low altitude, and stimulated chloride transport with a chloride-free solution containing amiloride and isoprenaline.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Two field studies reported successful prevention of HAPE in HAPE-susceptible climbers with inhalation of salmeterol, a long-acting β 2 -agonist [94], and oral dexamethasone [95] begun 1 day before ascent. Owing to multiple actions of β 2 -adrenergic agonists, such as inhibition of HPV, increased HVR and ventilation, tightening of cell-to-cell contacts and upregulation of NO production [96], the contribution of enhanced alveolar fluid clearance remains uncertain.…”
Section: Alveolar Fluid Clearancementioning
confidence: 99%
“…Based on a small, randomised trial [126] and extensive clinical experience, the pulmonary vasodilator nifedipine is the primary medication for this purpose. Other data demonstrate that the phosphodiesterase inhibitor tadalafil, dexamethasone [95] and the long-acting β 2 -agonist salmeterol [94] are also effective at preventing HAPE in known susceptible individuals, although the latter agent is less effective than pulmonary vasodilators and may be considered only for use as an adjunct to other agents and not as the sole prophylactic option [102]. The dose is also substantially higher than that used for asthma treatment and can lead to tachycardia and tremulousness.…”
Section: Pharmacological Measuresmentioning
confidence: 99%